Optimism and Pessimism of Stella Grant in Five Feet Apart Movie (2019) Based on Freud's Id, Ego, Superego Perspective - Fioren,; Maya Sekartaji, (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This thesis explores the psychological dimensions of optimism and pessimism in the character of Stella Grant from the film Five Feet Apart (2019). Utilizing Sigmund Freud’s psychoanalytic theory and concepts from positive and negative psychology, the research investigates how Stella’s optimistic and pessimistic traits influence her emotional growth and relationships while navigating life with cystic fibrosis. The study employs a descriptive qualitative method to analyze Stella’s coping mechanisms, emotional conflicts, and moments of resilience in the face of adversity. Through an in-depth examination of narrative structure, dialogue, and character development, this research provides insights into how psychological traits shape human experiences and enrich the storytelling of films. By bridging literature, film, and psychology, the findings contribute to a deeper understanding of how contrasting worldviews impact individual growth and foster emotional connections in challenging circumstances